2016
DOI: 10.1111/jre.12352
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal tissue engineering by nano beta‐tricalcium phosphate scaffold and fibroblast growth factor‐2 in one‐wall infrabony defects of dogs

Abstract: Japan Running titlePeriodontal healing by nano β-TCP and FGF-2 Key wordsPeriodontal tissue engineering, Fibroblast growth factor-2 (FGF-2), β-tricalcium phosphate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…The presentation and release of signaling molecules (such as growth factors) are also important for facilitating stem cell homing, proliferation, and differentiation. In this regard, growth/differentiation factor‐5 (e.g., see ), fibroblast growth factor‐2 (FGF‐2; e.g., see ), platelet‐derived growth factor‐BB (e.g., see ), and many other factors have already been used alone or in combination with various biomaterials for local cell manipulation and periodontal regeneration. Throughout the native regenerative response, different growth factors play multiple roles in specific release sequences and dosages; thus, the sequential release of multiple growth factors to mimic the normal biology of periodontal regeneration can lead to an enhanced outcome (e.g., see ).…”
Section: Harnessing Endogenous Stem Cells Via In Vivo Cell‐materials Imentioning
confidence: 99%
“…The presentation and release of signaling molecules (such as growth factors) are also important for facilitating stem cell homing, proliferation, and differentiation. In this regard, growth/differentiation factor‐5 (e.g., see ), fibroblast growth factor‐2 (FGF‐2; e.g., see ), platelet‐derived growth factor‐BB (e.g., see ), and many other factors have already been used alone or in combination with various biomaterials for local cell manipulation and periodontal regeneration. Throughout the native regenerative response, different growth factors play multiple roles in specific release sequences and dosages; thus, the sequential release of multiple growth factors to mimic the normal biology of periodontal regeneration can lead to an enhanced outcome (e.g., see ).…”
Section: Harnessing Endogenous Stem Cells Via In Vivo Cell‐materials Imentioning
confidence: 99%
“…47 Ogawa et al in 2016 48 stated that, nano-modification of biomaterials might increase the surface area and adsorption of signaling molecules. The observation from the above mentioned study confirms the bioactivity of the electrospinned PCL membranes reinforced with BG/Nhap and its usefulness in periodontal tissue engineering as a GTR/GBR membrane for proliferation and differentiation in to specific cell lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Nanomodification of biomaterials via nanosized bioceramics might play a major role in promoting their properties for biomedical applications [23][24][25][26] . Ibara et al and Ogawa et al prepared a 3D collagen scaffold with surfacemodifications using beta-tricalcium phosphate (β-TCP) nanoparticles and subsequently implanted the scaffold in combination with fibroblast growth factor-2 (FGF-2) into rat connective tissue 27,28) . They observed that the promotion of cell and tissue ingrowth into the scaffold was facilitated by β-TCP nanoparticle modification.…”
Section: Introductionmentioning
confidence: 99%